Ceramic composite material and method for producing the same

CN122916675APending Publication Date: 2026-10-16AERO ENGINE ACAD OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610955045.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有的陶瓷基复合材料在预冷器的特殊工况下,同时承受氧化与还原的极端化学氛围,现有材料的成分和结构设计均难以兼顾两侧壁面的差异化防护需求

Benefits of technology

与现有技术相比,本申请实施例中提供的一个或多个技术方案中,首先,陶瓷复合材料沿厚度方向具有外层、中间层和内层,外层、中间层和内层均包括碳化物基体以及弥散分布于碳化物基体中的自愈合相颗粒,碳化物基体包括HfC、ZrC、TiC、TaC和NbC。因此,本申请通过超高熔点的HfC、ZrC、TiC、TaC和NbC碳化物复配构建出碳化物基体骨架,使得材料整体具有超高的耐温能力、优异的结构强度与抗气流冲蚀能力。同时,弥散分布于基体中的自愈合相颗粒能够在材料受冷热交变产生微裂纹时,通过氧化生成玻璃相填充裂隙,实现裂纹原位封堵自愈,大幅提升材料的抗热震能力,有效缓解预冷器极端温差往复作用下裂纹的萌生与扩展问题。其次,本申请对自愈合相采用外层3%~8%、中间层12%~20%、内层5%~10%的梯度体积分数设计,外层自愈合相含量偏低,可避免自愈合相颗粒在高温氧化性气流中过快氧化耗竭,同时有利于外层碳化物基体快速生成致密复合氧化保护层;中间层自愈合相含量最高,可以在裂纹扩展路径上形成大量的反应位点,当裂纹延伸至该区域时,大量自愈合相可以快速氧化生成高黏度玻璃相,高效密封阻断裂纹向内贯穿,克服了均质掺杂自愈合相表层自愈合相颗粒过早损耗、后期修复能力不足的缺陷;内层自愈合相含量适中,既可保留基础裂纹修复作用,又能避免自愈合相与液氢中活性氢发生还原副反应,维持内层组织稳定。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916675A_ABST
    Figure CN122916675A_ABST
Patent Text Reader

Abstract

The application discloses a ceramic composite material and a preparation method thereof, and relates to the technical field of ceramic materials. The ceramic composite material has an outer layer, an intermediate layer and an inner layer along the thickness direction. The outer layer, the intermediate layer and the inner layer each comprise a carbide matrix and self-healing phase particles dispersedly distributed in the carbide matrix. The carbide matrix comprises HfC, ZrC, TiC, TaC and NbC. The volume fraction of the self-healing phase particles in the outer layer is 3-8%, the volume fraction of the self-healing phase particles in the intermediate layer is 12-20%, and the volume fraction of the self-healing phase particles in the inner layer is 5-10%. The molar fraction of Ta in the outer layer is less than that in the intermediate layer, and the molar fraction of Ta in the intermediate layer is less than that in the inner layer. The ceramic composite material and the preparation method can meet the protection requirements of the two sides of the pre-cooler wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ceramic materials technology, and in particular to a ceramic composite material and its preparation method. Background Technology

[0002] The precooler in a precooled engine has an outer wall that needs to withstand the scouring of high-temperature oxidizing gas flow, while its inner wall needs to be in direct contact with low-temperature liquid hydrogen. Therefore, the wall material of the precooler faces harsh challenges, and traditional high-temperature alloys can no longer meet the requirements in this environment.

[0003] Ceramic matrix composites are considered a major alternative to high-temperature alloys due to their high temperature resistance, low density, and good thermal shock resistance. However, under the special operating conditions of precoolers, existing ceramic matrix composites are subjected to extreme chemical atmospheres of both oxidation and reduction, and the composition and structural design of existing materials are insufficient to meet the differentiated protection requirements of the two side walls. Summary of the Invention

[0004] This application is made in view of the above-mentioned problems. The purpose of this application is to provide a ceramic composite material and its preparation method, which can simultaneously meet the differentiated protection requirements of oxidation resistance and reduction resistance on both sides of the precooler wall.

[0005] In a first aspect, this application provides a ceramic composite material, comprising: the ceramic composite material having an outer layer, an intermediate layer and an inner layer along the thickness direction, wherein the outer layer, the intermediate layer and the inner layer each include a carbide matrix and self-healing phase particles dispersed in the carbide matrix, and the carbide matrix includes HfC, ZrC, TiC, TaC and NbC. The volume fraction of self-healing phase particles in the outer layer is 3%~8%, in the middle layer it is 12%~20%, and in the inner layer it is 5%~10%. The mole fraction of Ta in the outer layer is less than that in the middle layer, and the mole fraction of Ta in the middle layer is less than that in the inner layer.

[0006] Secondly, this application also provides a method for preparing a ceramic composite material, comprising: Prepare the outer layer premix, the middle layer premix, and the inner layer premix separately; The inner layer premix, the middle layer premix and the outer layer premix are stacked in sequence and dried to obtain a gradient green body; Gradient green bodies are debinded and sintered to obtain ceramic composite materials; Compared with existing technologies, in one or more technical solutions provided in this application, the ceramic composite material firstly has an outer layer, a middle layer, and an inner layer along the thickness direction. The outer, middle, and inner layers all include a carbide matrix and self-healing phase particles dispersed within the carbide matrix. The carbide matrix includes HfC, ZrC, TiC, TaC, and NbC. Therefore, this application constructs a carbide matrix framework using a composite of ultra-high melting point HfC, ZrC, TiC, TaC, and NbC carbides, resulting in a material with ultra-high temperature resistance, excellent structural strength, and resistance to airflow erosion. Simultaneously, the self-healing phase particles dispersed within the matrix can fill microcracks through oxidation by generating a glassy phase when the material is subjected to alternating hot and cold temperatures, achieving in-situ crack sealing and self-healing. This significantly improves the material's thermal shock resistance and effectively alleviates the problem of crack initiation and propagation under extreme temperature fluctuations in the precooler. Secondly, this application employs a gradient volume fraction design for the self-healing phase, with an outer layer of 3%–8%, a middle layer of 12%–20%, and an inner layer of 5%–10%. The lower content of the self-healing phase in the outer layer prevents the self-healing phase particles from being rapidly oxidized and depleted in the high-temperature oxidizing gas flow, while also facilitating the rapid formation of a dense composite oxide protective layer in the outer carbide matrix. The middle layer has the highest content of self-healing phase, which can form a large number of reaction sites along the crack propagation path. When the crack extends to this region, a large amount of self-healing phase can be rapidly oxidized to generate a high-viscosity glass phase, effectively sealing and preventing the crack from penetrating inward. This overcomes the defects of premature loss of self-healing phase particles on the surface of homogeneous doped self-healing phases and insufficient later repair capabilities. The inner layer has a moderate content of self-healing phase, which can both retain the basic crack repair function and avoid the reduction side reaction between the self-healing phase and the active hydrogen in liquid hydrogen, thus maintaining the stability of the inner layer structure.

[0007] Meanwhile, this application sets the molar fraction of Ta element to increase gradually from the outer layer, through the middle layer, to the inner layer. The low Ta ratio in the outer layer facilitates the rapid formation of a dense and antioxidant oxide layer on the substrate, resisting oxidation by high-temperature combustion gases. The high Ta ratio in the inner layer enriches Ta2O5, which has stronger thermodynamic stability among the oxidation products. Compared with HfO2 and ZrO2, Ta2O5 is more difficult to be reduced and decomposed by hydrogen atmosphere, thus constructing a barrier against hydrogen reduction and hydrogen penetration in the inner layer, resisting liquid hydrogen reduction erosion and hydrogen embrittlement. The Ta element in the middle layer transitions smoothly, weakening the thermal expansion mismatch caused by abrupt changes in interlayer composition, reducing interfacial thermal stress, and inhibiting interlayer peeling cracking.

[0008] It is evident that the synergistic effect of the self-healing phase gradient distribution and the reverse gradient distribution of Ta element in this application enables the composite material to form functional zones along the thickness direction, including an outer layer for oxidation resistance, a middle layer for self-healing, and an inner layer for reduction resistance. The same material system can simultaneously adapt to the differentiated chemical atmospheres of oxidation and reduction on both sides of the precooler wall, achieving protection against extreme environments and significantly improving the long-term reliability and service life of the material. Attached Figure Description

[0009] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a schematic diagram of the structure of the ceramic composite material provided in the embodiments of this application; Figure 2 This is a flowchart illustrating the preparation process of ceramic composite materials provided in the embodiments of this application. Detailed Implementation

[0010] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative of this application and are not intended to limit this application.

[0011] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise expressly specified. "Several" means one or more, unless otherwise expressly specified.

[0012] In the description of this application, it should be understood that the terms "upper", "lower", "front", "rear", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0013] It should be noted that, in this application, the terms "exemplary" or "for example" are used to indicate that something is being described as an example, illustration, or illustration. Any embodiment or design described as "exemplary" or "for example" in this application should not be construed as being more preferred or advantageous than other embodiments or design solutions. Specifically, the use of terms such as "exemplary" or "for example" is intended to present the relevant concepts in a concrete manner.

[0014] In this application, "at least one" means one or more, and "more than one" means two or more. "And / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can mean: A alone, A and B simultaneously, or B alone, where A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects are in an "or" relationship. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, at least one of a, b, or c can mean: a, b, c, a combination of a and b, a combination of a and c, a combination of b and c, or a, b, and c, where a, b, and c can be single or multiple.

[0015] The precooled engine is a core component of the next-generation reusable aerospace propulsion system. It features a precooled combined cycle engine, and the precooler, a key component of this engine, withstands extreme thermochemical loads coupled with external ultra-high temperature oxidation and internal ultra-low temperature liquid hydrogen reduction. The stagnant gas temperature on the outer wall can reach 1500-2000K, rich in strong oxidizing components such as O2 and water vapor, while the inner wall directly contacts liquid hydrogen at around 20K, which vaporizes to form a high-hydrogen partial pressure reducing atmosphere. Therefore, the precooler's wall material faces stringent challenges, and traditional high-temperature alloys are no longer sufficient for this environment.

[0016] Ceramic matrix composites are considered a major alternative to high-temperature alloys due to their high temperature resistance, low density, and good thermal shock resistance. However, under the special operating conditions of precoolers, existing ceramic matrix composites are subjected to extreme chemical atmospheres of both oxidation and reduction, and the composition and structural design of existing materials are insufficient to meet the differentiated protection requirements of the two side walls.

[0017] Carbide matrices formed from HfC, ZrC, TiC, TaC, and NbC possess ultra-high melting points and excellent high-temperature strength, making them an important research direction in the field of ultra-high temperature thermal protection. Based on this, the introduction of dispersed self-healing phase particles can seal microcracks in the material by oxidizing and generating a glassy phase, further enhancing the material's resistance to thermal shock and high-temperature oxidation.

[0018] However, in existing technologies, the self-healing phase particles on the surface are largely consumed during early thermal cycling, rendering them ineffective in healing as cracks propagate deeper. Furthermore, the material exhibits the same oxidation and reduction resistance across all thickness directions, failing to provide zoned protection against the differences in oxidation and reduction atmospheres on either side of the precooler wall. These issues limit the long-life, reliable application of ceramic matrix composites on the walls of precooled engines.

[0019] To address the aforementioned issues, this application provides a ceramic composite material and its preparation method, which can meet the differentiated service requirements of the high-temperature oxidation environment on the outer wall of the precooler and the liquid hydrogen reduction environment on the inner wall, thus solving the technical shortcomings of conventional homogeneous ceramics in terms of premature depletion of the self-healing phase and the inability to simultaneously address both sides of corrosion protection.

[0020] This application provides a ceramic composite material. Figure 1 A schematic diagram of the structure of the ceramic composite material provided in the embodiments of this application is shown, such as... Figure 1 As shown, the ceramic composite material has an outer layer 110, a middle layer 120 and an inner layer 130 along the thickness direction. The outer layer 110, the middle layer 120 and the inner layer 130 all include a carbide matrix and self-healing phase particles dispersed in the carbide matrix. The carbide matrix includes HfC, ZrC, TiC, TaC and NbC.

[0021] This application utilizes a composite of HfC, ZrC, TiC, TaC, and NbC to form a carbide matrix framework, giving the composite material exceptionally high temperature resistance, excellent structural strength, and resistance to airflow erosion. Simultaneously, the self-healing phase particles dispersed within the matrix can, when microcracks arise due to alternating thermal temperatures, oxidize to generate a glassy phase that fills the cracks, achieving in-situ crack sealing and self-healing. This significantly enhances the material's thermal shock resistance and effectively mitigates the initiation and propagation of cracks under extreme temperature fluctuations in the precooler.

[0022] It should be noted that the aforementioned carbide matrix is ​​a single-phase high-entropy carbide formed by solid solution of five transition metal carbides: HfC, ZrC, TiC, TaC, and NbC. The crystal structure is rock salt, with a space group of Fm-3m. These five carbides share the same crystal structure type and similar lattice constants, allowing them to form continuous solid solutions. The high-entropy effect effectively suppresses phase separation and grain coarsening of the carbides at high temperatures, maintaining structural stability over a wide temperature range. Simultaneously, the presence of Hf, Zr, Ti, Ta, and Nb of different atomic sizes within the same lattice causes local lattice distortion, increasing the resistance to dislocation movement. This enhances the material's room-temperature toughness and high-temperature creep resistance, resulting in a composite material with excellent high-temperature strength, thermal shock resistance, and structural stability.

[0023] In some examples, the volume fraction of self-healing phase particles in the outer layer 110 of the above-mentioned ceramic composite material is 3% to 8%, the volume fraction of self-healing phase particles in the middle layer 120 is 12% to 20%, and the volume fraction of self-healing phase particles in the inner layer 130 is 5% to 10%.

[0024] This application employs a gradient volume fraction design for the self-healing phase, with the outer layer at 110%~8%, the middle layer at 120%~20%, and the inner layer at 130%~10%, ensuring that the content of the self-healing phase in each layer matches the service environment of each layer. The outer layer 110 is directly exposed to high-temperature, high-speed oxidizing gas flow. Controlling its volume fraction in the low range of 3%~8% can slow down the oxidation depletion rate of the self-healing phase and extend the overall self-healing service life. At the same time, it reduces the interference of the second phase on the formation of a continuous high-entropy carbide oxide film, promoting the rapid formation of a dense and continuous multi-element composite oxide protective layer on the substrate, effectively isolating the continuous inward erosion of external oxygen and water vapor. The intermediate layer 120 is located in the essential channel for crack propagation from the outside to the inside, and is the core functional layer for crack arrest and protection of the material. Therefore, the highest self-healing phase volume fraction is set at 12%~20%. When microcracks caused by alternating hot and cold temperatures penetrate the outer layer 110 and extend to the intermediate layer 120, the large amount of diffusely distributed self-healing phase can simultaneously react with the infiltrated oxygen to rapidly generate a high-viscosity glass phase, which fully fills and seals the crack channel, effectively preventing the diffusion of fracture oxygen media to the inner layer 130 of the material. This avoids the premature depletion of self-healing phase particles on the homogeneous ceramic surface and the inability to seal deep cracks. The inner layer 130 is attached to the cryogenic liquid hydrogen side, taking into account both hydrogen reduction resistance and basic self-healing requirements. Therefore, the self-healing phase volume fraction is set in the medium range of 5%~10%, which can retain the basic crack sealing ability, while reducing the reduction side reaction between the self-healing phase and the active hydrogen generated by the vaporization of liquid hydrogen, maintaining the long-term stability of the inner layer 130 structure.

[0025] For example, in the above-mentioned ceramic composite material, the molar fraction of Ta in the outer layer 110 is less than the molar fraction of Ta in the middle layer 120, and the molar fraction of Ta in the middle layer 120 is less than the molar fraction of Ta in the inner layer 130.

[0026] In this application, the molar fraction of Ta increases gradually from the outer layer 110, through the middle layer 120, to the inner layer 130. The outer layer 110 directly faces the high-temperature oxidizing gas flow of 1500~2000K. The low Ta molar fraction design reduces the proportion of TaC in the matrix, promoting the rapid formation of a continuous and dense composite oxide film composed of HfO2, ZrO2, TiO2, and Nb2O5 after the oxidation of the high-entropy carbide matrix. This multi-element oxide layer has high density and strong adhesion, effectively blocking the penetration of oxygen and high-temperature water vapor into the material interior, resisting the continuous erosion of high-speed, high-temperature gas flow, and avoiding rapid oxidation and loss of the surface layer. The inner layer 130 is close to the low-temperature liquid hydrogen heat exchange interface. After vaporization, it forms a high hydrogen partial pressure and strong reducing atmosphere. The higher Ta molar fraction can increase the proportion of TaC in the matrix, and after oxidation, Ta2O5 with excellent thermodynamic stability is enriched at the interface. Compared with HfO2 and ZrO2, Ta2O5 has a more corrected Gibbs free energy for hydrogen reduction reactions. It is not easily reduced and decomposed by H2 in a hydrogen-rich low-temperature environment. It can form a stable hydrogen barrier in the inner layer 130, blocking active hydrogen atoms from diffusing inward along grain boundaries and microcracks, and inhibiting failure behaviors such as hydrogen-induced cracking, matrix pulverization, and hydrogen embrittlement. Thus, it is suitable for the long-term reducing service environment of the precooler inner wall.

[0027] Based on this, since the intrinsic thermal expansion coefficient of TaC is higher than that of HfC, ZrC, TiC, and NbC, simply increasing the Ta content will increase the thermal expansion coefficient of the matrix. Therefore, this application uses the intermediate layer 120 as a transition buffer layer to gradually increase the molar fraction of Ta, avoiding drastic changes in composition between the outer layer 110 and the inner layer 130. This significantly reduces the residual interfacial stress caused by the interlayer thermal expansion mismatch during thermal cycling and effectively suppresses defects such as interlayer transverse cracks, interfacial peeling, and flaking.

[0028] For example, the molar fraction of Ta in the outer layer 110 is 0.15~0.20, the molar fraction of Ta in the middle layer 120 is 0.20~0.25, and the molar fraction of Ta in the inner layer 130 is 0.25~0.35. Through the gradient design of the Ta elements in the above three layers, this application achieves a compositional gradient distribution along the thickness direction: the outer layer 110 is oxidation-resistant, the middle layer 120 is a transition buffer, and the inner layer 130 is reduction-resistant. The same material system can simultaneously adapt to the differentiated chemical atmospheres of oxidation and reduction on both sides of the precooler wall.

[0029] In some examples, the molar fractions of HfC, ZrC, TiC, TaC, and NbC in the aforementioned carbide matrix are 0.20–0.30, 0.15–0.25, 0.10–0.20, 0.25–0.35, and 0.10–0.20, respectively, and the sum of the molar fractions of HfC, ZrC, TiC, TaC, and NbC is 1. Within this compositional range, the five carbides have similar lattice constants and the same rock salt structure type, enabling them to form stable single-phase solid solutions over a wide temperature range, avoiding the adverse effects of second-phase precipitation on material properties. Simultaneously, HfC, ZrC, and TiC possess low vapor pressures and excellent high-temperature oxidation-resistant products (HfO2, ZrO2, TiO2), providing good high-temperature oxidation resistance to the matrix; while TaC and NbC enhance the high-temperature strength and creep resistance of the matrix through solid solution strengthening effects. The synergistic combination of the above five carbides gives the high-entropy carbide matrix excellent temperature resistance, structural stability and mechanical properties.

[0030] In some examples, when applied to the outer layer 110, the molar fractions of HfC, ZrC, TiC, TaC, and NbC are 0.25–0.30, 0.15–0.20, and 0.15–0.20, respectively. The higher HfC and ZrC ratios in the outer layer 110 facilitate the formation of a composite oxide layer with higher HfO2 and ZrO2 content during oxidation. HfO2 and ZrO2 possess extremely high melting points and excellent high-temperature chemical stability, significantly enhancing the outer layer 110's resistance to erosion and its long-term antioxidant protection performance in high-temperature oxidizing gas streams.

[0031] In some examples, when applied to the intermediate layer 120, the molar fractions of HfC are 0.22–0.28, ZrC is 0.17–0.22, TiC is 0.12–0.18, TaC is 0.20–0.25, and NbC is 0.12–0.18. The intermediate layer 120 serves as a compositional transition buffer layer, with the molar fractions of each carbide falling between those of the outer layer 110 and the inner layer 130. This ensures good compositional compatibility and interfacial bonding strength with adjacent layers, while also providing a suitable self-healing environment for the intermediate layer 120, ensuring rapid response and efficient plugging when cracks extend to it.

[0032] In some examples, when applied to the inner layer 130, the molar fractions of HfC are 0.20–0.25, ZrC is 0.15–0.20, TiC is 0.10–0.15, TaC is 0.25–0.35, and NbC is 0.10–0.15. The higher TaC ratio in the inner layer 130 facilitates the enrichment of Ta₂O₅ in the oxide layer, enhancing its resistance to hydrogen reduction in a liquid hydrogen reducing atmosphere.

[0033] It should be noted that the above range of molar fractions of each carbide is only an example. Those skilled in the art can independently adjust the molar fraction of each carbide within the above range according to the specific design value of the molar fraction of Ta in each layer and the influence of Hf, Zr, Ti and Nb on the matrix lattice parameters, thermal expansion coefficient and oxidation resistance, so as to meet the needs of different service environments and preparation processes.

[0034] In some examples, the self-healing phase particles are selected from SiC particles and / or Si3N4 particles. Both SiC and Si3N4 can generate a molten SiO2 glass phase in a high-temperature oxidizing environment. This molten SiO2 glass phase has suitable viscosity and good fluidity, allowing it to penetrate along microcracks and fill the cracks under capillary action, achieving effective crack sealing. Si3N4 has a higher oxidation rate than SiC, and can generate the SiO2 glass phase more quickly at the same temperature, making it suitable for the intermediate layer 120, which requires a high self-healing response speed. SiC, on the other hand, has a relatively mild oxidation rate, resulting in a denser SiO2 layer, making it suitable for the outer layer 110 and inner layer 130, which require long-term stable oxidation protection. This application allows for the independent selection of SiC or Si3N4 as the self-healing phase in each layer based on the service environment and self-healing response speed requirements, achieving customized self-healing performance for each layer.

[0035] For example, the outer layer 110 may use SiC particles as the self-healing phase, the middle layer 120 may use Si3N4 particles as the self-healing phase, and the inner layer 130 may use SiC particles as the self-healing phase. Alternatively, the outer layer 110, the middle layer 120, and the inner layer 130 may all use SiC particles as the self-healing phase. Alternatively, the outer layer 110, the middle layer 120, and the inner layer 130 may all use Si3N4 particles as the self-healing phase.

[0036] In some examples, the average particle size of the self-healing phase particles in the inner layer 130 is larger than that in the intermediate layer 120. The inner layer 130 of this application uses larger-diameter self-healing phase particles, which have a smaller specific surface area per unit volume and a lower initial oxidation rate in high-temperature environments. This helps to delay the unnecessary consumption of the self-healing phase in the early stages of service, allowing the inner layer 130 to maintain effective crack repair capabilities in the later stages of service. Simultaneously, the larger particle size provides a larger contact area and a more significant difference in thermal expansion between the large-diameter particles and the surrounding carbide matrix. During cooling, this creates a beneficial residual compressive stress field around the particles, which to some extent offsets the thermal expansion stress concentration caused by the high Ta content in the inner layer 130, reducing the tendency for microcrack initiation in the inner layer 130. The intermediate layer 120 uses medium-diameter self-healing phase particles, balancing oxidation reactivity and crack filling efficiency. This allows for rapid oxidation to generate a sufficient amount of glassy phase when cracks extend from the outer layer 110 to the intermediate layer 120, achieving efficient sealing. The outer layer 110 uses small-diameter self-healing phase particles. Its high specific surface area allows it to have a faster initial oxidation rate in a high-temperature oxidizing environment, which is beneficial for the outer layer 110 to quickly form a dense oxide protective layer in the early stage of service.

[0037] For example, the average particle size of the self-healing phase particles in the outer layer 110 is 1 μm to 5 μm, the average particle size of the self-healing phase particles in the middle layer 120 is 5 μm to 15 μm, and the average particle size of the self-healing phase particles in the inner layer 130 is 15 μm to 30 μm.

[0038] Since the outer layer 110 of the ceramic composite material in this application is directly exposed to high-temperature, high-speed oxidizing gas flow, fine-grained self-healing phase particles of 1μm to 5μm are selected. These particles can be uniformly dispersed at the grain boundaries of the five-element high-entropy carbides without disrupting the continuous matrix framework, thus ensuring the high-temperature strength and erosion resistance of the matrix. Simultaneously, the large specific surface area of ​​the fine particles allows for the uniform and simultaneous generation of the SiO2 glass phase during high-temperature oxidation, assisting the matrix in rapidly spreading and forming a complete and dense multi-element composite oxide protective layer. Compared to the fine particles of the outer layer 110, the intermediate layer 120 uses medium-sized particles of 5μm to 15μm. The gaps formed by these medium-sized particles provide flow channels for the molten glass phase, allowing it to fully penetrate deep into the cracks through capillary action, achieving complete sealing of wide and deep microcracks. The inner layer 130 is in long-term contact with the highly reducing hydrogen atmosphere formed by the vaporization of liquid hydrogen. It uses large-particle-size self-healing phase particles of 15μm~30μm, which have a lower specific surface area per unit volume. This can significantly reduce the contact area between the self-healing phase and active hydrogen atoms, effectively suppress the reduction side reaction between SiC or Si3N4 and hydrogen, and avoid defects such as pulverization and porosity in the inner layer 130.

[0039] In addition, the three layers with different particle sizes can avoid the problems of local porosity and stress concentration caused by the large difference in particle size at the interface of different layers. The interlayer particles interpenetrate and interlock with each other, thereby improving the interfacial bonding strength of the three-layer gradient structure and further enhancing the overall thermal shock resistance and peel resistance of the composite material.

[0040] In some examples, the inner layer 130 of this application embodiment also contains rare earth silicates. Introducing rare earth silicates into the inner layer 130 has several advantages. First, rare earth silicates have a low intrinsic coefficient of thermal expansion, which can offset the increase in the coefficient of thermal expansion caused by the high Ta content of the inner layer 130. This results in the overall effective coefficient of thermal expansion of the inner layer 130 being between that of the high-entropy carbide matrix and the self-healing phase particles, forming a thermal expansion gradient transition. This alleviates the interfacial thermal stress between the coating and the substrate, and inhibits interfacial debonding and cracking under thermal cycling. Second, rare earth silicates can react with SiO2 in a high-temperature oxidizing environment to form a dense rare earth silicate glass phase. This glass phase has excellent thermochemical stability and low oxygen permeability, which can further enhance the inner layer 130's resistance to hydrogen permeation and high-temperature water vapor corrosion, and improve the long-term structural stability of the inner layer 130 in a reducing atmosphere. In addition, rare earth silicate particles are dispersed as a second phase in the inner 130 carbide matrix, which can suppress grain boundary migration through the particle pinning effect, hinder grain coarsening at high temperature, and maintain the stability of the inner 130 microstructure.

[0041] In some examples, the volume fraction of rare earth silicates in the inner layer 130 of this application embodiment is 3% to 8%. Within this volume fraction range, rare earth silicates can fully utilize their low thermal expansion characteristics to effectively offset the increase in the coefficient of thermal expansion caused by the high Ta content in the inner layer 130, resulting in a good match between the overall coefficient of thermal expansion of the inner layer 130 and the self-healing phase particle substrate, thereby significantly reducing interfacial thermal stress. Simultaneously, an appropriate amount of rare earth silicate particles dispersed in the carbide matrix of the inner layer 130 can inhibit grain boundary migration through the pinning effect, hindering grain coarsening at high temperatures and maintaining the microstructure stability of the inner layer 130. Furthermore, this content range ensures that the continuity of the carbide matrix is ​​not disrupted, avoiding mechanical property degradation caused by excessive aggregation of the second phase, thus achieving a good comprehensive balance between thermal expansion matching, structural stability, and mechanical properties in the inner layer 130.

[0042] For example, the rare earth silicates mentioned above are selected from one or more of Y2SiO5, Y2Si2O7, Lu2SiO5, and Lu2Si2O7.

[0043] As a further example, the inner layer 130 may also have an additional 1% to 3% SiO2 micro powder by volume. During the sintering process, the SiO2 micro powder can undergo a solid-state reaction with rare earth silicates in situ to generate rare earth disilicates (Y2Si2O7, Lu2Si2O7) with lower thermal expansion coefficient and better chemical stability, thereby further enhancing the thermal expansion compensation effect.

[0044] In some examples, the outer layer 110 of the ceramic composite material of this application also has a pore structure, which is a continuous interconnected micropore structure.

[0045] It should be noted that this continuous, interconnected microporous structure is formed by the thermal decomposition of graphite powder added to the outer layer 110 during sintering. In the initial oxidation stage of the ceramic composite material during its first service, the oxidizing atmosphere can rapidly penetrate the outer layer 110 along this continuous, interconnected microporous network, thereby promoting the comprehensive oxidation of the carbide matrix of the outer layer 110 from the surface inwards and accelerating the formation of a dense composite oxide layer. As the oxidation reaction proceeds, the SiO2 glass phase generated by the oxidation of the self-healing phase can gradually fill the micropores, achieving self-sealing and densification of the outer layer 110. This shortens material loss during the initial oxidation stage and improves the early protection efficiency of the composite material.

[0046] In some alternative configurations, the outer layer 110 has a thickness of 0.5 mm to 2.0 mm, the intermediate layer 120 has a thickness of 1.0 mm to 5.0 mm, and the inner layer 130 has a thickness of 0.1 mm to 0.5 mm. In this application, the outer layer 110 is designed to have a thickness of 0.5 mm to 2.0 mm. This thickness range is sufficient to ensure that the outer layer 110 forms a continuous and complete composite oxide protective layer in a high-temperature oxidizing gas flow, while avoiding the accumulation of interfacial thermal stress and delayed self-healing response caused by excessive thickness. The intermediate layer 120, as the core functional layer for crack arrest, has a thickness of 1.0 mm to 5.0 mm, providing sufficient crack sealing capacity. When a crack penetrates the outer layer 110 and extends to the intermediate layer 120, the thicker intermediate layer 120 can accommodate more self-healing phase particles to participate in the oxidation reaction, ensuring sufficient sealing of wide and deep cracks. The inner 130 layer is bonded to the cryogenic liquid hydrogen side, with a thickness of 0.1mm~0.5mm. While meeting the requirements for resistance to hydrogen reduction and thermal expansion transition, it can avoid the decrease in heat conduction efficiency and interface stress concentration caused by excessive thickness.

[0047] In one feasible embodiment, this application provides a method for preparing a ceramic composite material. Figure 2 A flowchart illustrating a method for preparing ceramic composite materials according to an embodiment of this application is shown. Figure 2 As shown, the method for preparing the ceramic composite material in this application includes: Step 201: Prepare outer layer premix, middle layer premix and inner layer premix using carbide matrix and self-healing phase particles respectively.

[0048] It is understandable that the aforementioned outer layer premix is ​​used to form the outer layer of the ceramic composite material, the middle layer premix is ​​used to form the middle layer of the ceramic composite material, and the inner layer premix is ​​used to form the inner layer of the ceramic composite material.

[0049] It should be noted that the aforementioned outer, middle, and inner premixes all include a carbide matrix and self-healing phase particles dispersed within the carbide matrix. The carbide matrix includes HfC, ZrC, TiC, TaC, and NbC. Furthermore, the volume fraction of the self-healing phase particles in the outer premix is ​​3%–8%, in the middle premix is ​​12%–20%, and in the inner premix is ​​5%–10%. Additionally, the molar fraction of Ta in the outer premix is ​​less than that in the middle premix, and the molar fraction of Ta in the middle premix is ​​less than that in the inner premix.

[0050] This application involves separately formulating outer, intermediate, and inner layer premixes with different self-healing phase contents and Ta molar fractions, allowing the composition and structure of each premix to be independently controlled according to its preset service function. For example, the outer layer premix has a low self-healing phase content (3%~8%), which prevents the surface self-healing phase from being depleted too quickly in the high-temperature oxidizing gas flow, and at the same time facilitates the rapid formation of a dense composite oxide protective layer on the outer carbide matrix. The intermediate layer premix has the highest self-healing phase content (12%~20%), which ensures that sufficient self-healing reaction sites are available when cracks penetrate the outer layer and extend to the intermediate layer, achieving efficient crack sealing. The inner layer premix has a moderate self-healing phase content (5%~10%), which can retain basic self-healing capabilities while reducing side reactions with the reducing atmosphere of liquid hydrogen. Meanwhile, the molar fraction of Ta increases sequentially from the outer layer to the inner layer. The low Ta content in the outer layer facilitates the formation of a dense oxide layer dominated by HfO2 and ZrO2, while the high Ta content in the inner layer enriches the oxidation products with Ta2O5, which has excellent thermodynamic stability, thus constructing an anti-hydrogen reduction barrier in the inner layer. The gradual transition of Ta content in the middle layer effectively mitigates the interlayer thermal expansion mismatch. By utilizing the above three-layer premix, the ceramic composite material after subsequent lamination achieves, in principle, synergistic protection of the outer layer against oxidation, the middle layer against cracking and self-healing, and the inner layer against reduction. This allows the same material system to simultaneously adapt to the different chemical atmospheres on both sides of the precooler wall.

[0051] In some examples, the above-mentioned preparation of outer layer premix, intermediate layer premix, and inner layer premix using a carbide matrix and self-healing phase particles specifically includes: First, preparing outer layer mixed powder, intermediate layer mixed powder, and inner layer mixed powder using a carbide matrix and self-healing phase particles respectively. Then, ball milling and mixing the outer layer mixed powder, intermediate layer mixed powder, and inner layer mixed powder separately to obtain outer layer slurry, intermediate layer slurry, and inner layer slurry. Next, drying and sieving the outer layer slurry, intermediate layer slurry, and inner layer slurry separately to obtain outer layer premix, intermediate layer premix, and inner layer premix.

[0052] For example, the above-mentioned preparation of outer layer mixed powder, middle layer mixed powder and inner layer mixed powder using carbide matrix and self-healing phase particles respectively includes: First, weighing HfC, ZrC, TiC, TaC and NbC powder and self-healing phase particles according to the proportions of 3%~8% volume fraction of self-healing phase particles in the outer layer, 1μm~5μm average particle size of self-healing phase particles in the outer layer, and 0.15~0.20 molar fraction of Ta element in the outer layer, and adding graphite micro powder (the volume fraction of graphite micro powder in the outer layer mixed powder is 1%~6%), and mixing to obtain the outer layer mixed powder. Then, according to the proportions of 12%~20% volume fraction of self-healing phase particles in the intermediate layer, 5μm~15μm average particle size of self-healing phase particles in the intermediate layer, and 0.20~0.25 molar fraction of Ta element in the intermediate layer, HfC, ZrC, TiC, TaC and NbC powders and self-healing phase particles are weighed and mixed to obtain intermediate layer mixed powder. Next, according to the proportions of 5%~10% volume fraction of self-healing phase particles in the inner layer, 15μm~30μm average particle size of self-healing phase particles in the inner layer, and 0.25~0.35 molar fraction of Ta element in the inner layer, HfC, ZrC, TiC, TaC and NbC powders and self-healing phase particles were weighed, and rare earth silicates (3%~8% volume fraction of rare earth silicates in the inner layer mixed powder) and SiO2 micro powder (1%~3% volume fraction of SiO2 micro powder in the inner layer mixed powder) were added and mixed to obtain the inner layer mixed powder.

[0053] This application formulates outer layer mixed powder, middle layer mixed powder and inner layer mixed powder according to the preset volume fraction of self-healing phase, particle size, molar fraction of Ta element and type of additives for each layer. The composition and structural characteristics of each layer of powder are differentiated and determined in the mixing stage, thus providing a material basis for subsequent stacking to form a gradient structure.

[0054] For example, the above-mentioned process of ball milling and mixing the outer layer mixed powder, the middle layer mixed powder, and the inner layer mixed powder to obtain the outer layer slurry, the middle layer slurry, and the inner layer slurry specifically includes: adding the outer layer mixed powder, the middle layer mixed powder, and the inner layer mixed powder, respectively, to a ball milling jar with a solvent and a grinding medium, and performing high-energy ball milling and mixing on a planetary ball mill to obtain the outer layer slurry, the middle layer slurry, and the inner layer slurry, respectively.

[0055] For example, the solvent mentioned above is anhydrous ethanol or acetone, and the grinding media is tungsten carbide balls or zirconia balls. Both anhydrous ethanol and acetone have low surface tension and good volatility, effectively wetting the surface of powder particles during ball milling, promoting uniform particle dispersion. Simultaneously, they evaporate rapidly during subsequent drying, avoiding any residue that could adversely affect material properties. Tungsten carbide balls and zirconia balls have high hardness and high wear resistance, and are not easily worn away during ball milling, preventing the introduction of impurities that contaminate the slurry due to wear of the grinding media themselves.

[0056] For example, the ball milling speed is 300 rpm to 500 rpm, the ball-to-powder ratio is 5:1 to 15:1, and the milling time is 10 hours to 48 hours. Within this speed range, the grinding balls can obtain sufficient kinetic energy to effectively crush and mix the powder particles, while avoiding excessive grinding and increased media wear caused by excessively high speeds. A ball-to-powder ratio controlled within the range of 5:1 to 15:1 provides sufficient collision frequency between the grinding media and the powder to ensure uniform mixing, without reducing milling efficiency or increasing energy consumption due to an excessively high ball-to-powder ratio. A milling time of 10 hours to 48 hours ensures that carbide particles and self-healing phase particles in each layer of powder are fully crushed to the preset particle size and uniformly mixed, while avoiding excessive particle refinement or cold-welded agglomeration caused by prolonged milling.

[0057] Through the ball milling mixing process described above, the carbide particles and self-healing phase particles in each layer of powder can be uniformly dispersed at the nanoscale, ensuring the uniformity of the composition and the consistency of the structure of each layer of premix, which provides a guarantee for obtaining a gradient structure composite material with uniform structure and stable performance through subsequent casting and sintering.

[0058] Step 202: The inner layer premix, the middle layer premix and the outer layer premix are stacked sequentially to form a gradient green body after drying.

[0059] For example, a multilayer casting process can be used. First, the inner layer premix is ​​made into a casting slurry and cast on the substrate to form an inner layer green blank. After the inner layer green blank is dried to a certain strength, the casting slurry made from the middle layer premix is ​​cast on the inner layer green blank to form a middle layer green blank. Finally, the casting slurry made from the outer layer premix is ​​cast on the middle layer green blank to form an outer layer green blank. After drying, a gradient green blank with inner, middle and outer layers stacked in sequence is obtained.

[0060] In the aforementioned layered forming process, the inner, middle, and outer green bodies are bonded together through the interpenetration of powder particles in the slurry, eliminating the need for an additional adhesive layer. This sequential layering ensures a continuous transition of composition and structure at the interfaces of each layer, avoiding interface defects caused by layered preparation and secondary assembly. In the resulting gradient green bodies after drying, the content of self-healing phase particles, the molar fraction of Ta, and the particle size of each layer exhibit a predetermined gradient distribution along the thickness direction, providing a foundation for the formation of a complete functional gradient structure after subsequent sintering.

[0061] Step 203: Perform debinding and sintering on the gradient green body to obtain ceramic composite material.

[0062] For example, the above-mentioned process of debinding and sintering gradient green bodies to obtain ceramic composite materials includes: debinding the gradient green bodies at 600℃~800℃ in a vacuum or inert atmosphere to obtain debinded green bodies, wherein the debinding time is 1 hour~3 hours; sintering the debinded green bodies at a temperature of 1800℃~2200℃ and a pressure of 30MPa~100MPa using spark plasma sintering technology, and holding at that temperature for 10 minutes~60 minutes to obtain ceramic composite materials.

[0063] The above-mentioned debinding process can be carried out in a vacuum or inert atmosphere, which avoids the oxidation reaction between the organic binder and the carbide matrix during decomposition, ensuring that the chemical composition and phase structure of the matrix remain unchanged. The debinding temperature is controlled at 600℃~800℃, ensuring sufficient decomposition and removal of organic components without causing significant grain growth or coarsening of the green body during the debinding stage due to excessive temperature. The debinding time is 1 hour~3 hours, ensuring complete decomposition of organic matter while avoiding increased energy consumption and reduced efficiency caused by prolonged debinding.

[0064] The aforementioned spark plasma sintering can be performed in a graphite mold. The temperature range of 1800℃ to 2200℃ is lower than that required for traditional pressureless sintering (typically higher than 2200℃), effectively suppressing abnormal grain growth in the carbide matrix and ensuring the fine-grained structure of the high-entropy carbide matrix. The sintering pressure is 30MPa to 100MPa, providing sufficient densification driving force while avoiding mold deformation or green body cracking caused by excessive pressure. The holding time is 10 minutes to 60 minutes. Combined with the rapid densification characteristics of spark plasma sintering, this prevents the grains from undergoing significant coarsening during sintering, maintaining the fine-grained strengthening effect of the matrix.

[0065] Through the above-mentioned debinding and sintering processes, the pre-set self-healing phase content gradient, particle size gradient, Ta element molar fraction gradient and rare earth silicate distribution in each layer of the gradient green body can be completely preserved. The interlayer is metallurgically bonded through high-temperature sintering, and finally a dense ceramic composite material with functional gradient structure can be obtained.

[0066] It should be noted that the graphite micropowder in the aforementioned outer layer mixed powder can thermally decompose during sintering to form continuous interconnected micropores. These continuous interconnected micropores can guide the oxidizing atmosphere to penetrate from the outer layer surface inward during the initial oxidation process of the composite material, promoting the rapid oxidation of the outer carbide matrix to form a dense composite oxide skin. Subsequently, the continuous interconnected micropores are filled with the SiO2 glass phase generated by the oxidation of the self-healing phase, achieving self-sealing and densification of the outer layer. In addition, controlling the volume fraction of graphite micropowder in the outer layer within the range of 1% to 6% can form an appropriate amount of micropore network to achieve rapid oxidation and skin formation and self-sealing functions, while avoiding pore defects and structural strength reduction caused by excessive pore-forming agent residue. This achieves a good balance between initial oxidation protection efficiency and long-term structural integrity of the outer layer.

[0067] To verify the effectiveness of the ceramic composite material provided in the embodiments of this application, this application uses a comparison of embodiments and comparative examples for demonstration.

[0068] Example 1 Embodiment 1 of this application provides a method for preparing a ceramic composite material, comprising the following steps: The first step is the preparation of the mixed powders for each layer. The outer layer mixed powder is prepared according to the outer layer carbide matrix Hf0. 20 Zr0. 20 Ti0. 20 Ta0. 18 Nb0. 22 The proportion of C is as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 3μm are added as a self-healing phase to make the volume fraction of SiC particles in the outer layer 5%. Graphite powder is also added, with the volume fraction of graphite powder in the outer layer mixed powder being 3%.

[0069] Intermediate layer mixed powder: based on intermediate layer carbide matrix Hf0. 20 Zr0. 20 Ti0. 17 Ta0. 22 Nb0. 21 The proportions of C are as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 10μm are added as a self-healing phase, so that the volume fraction of SiC particles in the intermediate layer is 16%.

[0070] Inner layer mixed powder: based on inner layer carbide matrix Hf0. 20 Zr0. 20 Ti0. 15 Ta0. 28 Nb0. 17 The proportions of C are as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 20μm are added as a self-healing phase to make the volume fraction of SiC particles in the inner layer 7%. Y2SiO5 powder and SiO2 micro powder are also added. The volume fraction of Y2SiO5 powder in the inner layer mixed powder is 6%, and the volume fraction of SiO2 micro powder in the inner layer mixed powder is 2%.

[0071] In this embodiment, the mole fractions of Ta in the outer, middle, and inner layers are 0.18, 0.22, and 0.28, respectively, satisfying a gradient relationship that increases sequentially from the outer layer to the inner layer. The volume fractions of SiC particles in the outer, middle, and inner layers are 5%, 16%, and 7%, respectively, satisfying a gradient distribution with low concentration in the outer layer, high concentration in the middle layer, and moderate concentration in the inner layer. The average particle sizes of SiC particles in the outer, middle, and inner layers are 3 μm, 10 μm, and 20 μm, respectively, satisfying a particle size gradient distribution that increases sequentially from the outer layer to the inner layer.

[0072] In the second step, the outer layer mixed powder, middle layer mixed powder, and inner layer mixed powder were added to a ball mill jar with anhydrous ethanol and tungsten carbide grinding balls, respectively. The mixtures were then ball-milled at 400 rpm for 24 hours in a planetary ball mill with a ball-to-powder ratio of 10:1, yielding outer layer slurry, middle layer slurry, and inner layer slurry, respectively. These slurries were then dried in a vacuum drying oven at 80°C for 12 hours and passed through a 100-mesh sieve to obtain outer layer premix, middle layer premix, and inner layer premix, respectively.

[0073] The third step involves preparing casting slurries from the outer, middle, and inner premixes, respectively. These slurries are then sequentially cast onto the substrate using a multilayer casting process (first the inner layer, then the middle layer, and finally the outer layer). After drying, a gradient green body is obtained. The outer layer has a thickness of 1.0 mm, the middle layer has a thickness of 3.0 mm, and the inner layer has a thickness of 0.3 mm.

[0074] The fourth step involves debinding the aforementioned gradient green body at 700°C for 2 hours in an Ar atmosphere to obtain a debinded green body. This debinded green body is then placed into a graphite mold and densified using spark plasma sintering: the sintering temperature is 2000°C, the sintering pressure is 50 MPa, the holding time is 30 minutes, and the vacuum degree is 10. -3 Pa, with a heating rate of 100℃ / min, yielded a ceramic composite material.

[0075] Based on the above proportions and processes, the resulting high-entropy carbide matrix of the ceramic composite material is a single-phase solid solution with a rock salt structure (space group Fm-3m), without the precipitation of a second-phase carbide. During sintering, the outer layer of graphite micropowder thermally decomposes to form a continuous, interconnected microporous network. The middle layer contains uniformly dispersed SiC particles, and the inner layer contains Y2SiO5 and SiO2 micropowder that react in situ during sintering to form the Y2Si2O7 phase. Based on the mixing principle of multiphase materials, the effective thermal expansion coefficient of the inner layer in this embodiment is estimated to be approximately 5.5~6.5×10⁻⁶. -6 K - ¹, between high-entropy carbide matrix (approximately 7.5 × 10⁻⁶) -6 K - ¹) with SiC / SiC substrate (approximately 5.0 × 10⁻⁶) -6 K - Between ¹), a thermal expansion gradient transition interface is formed, which helps to alleviate the interfacial thermal stress between the coating and the substrate. Under thermal cycling conditions, when the outer microcracks propagate into the middle layer, the high volume fraction of SiC particles in the middle layer can be rapidly oxidized to generate the SiO2 glass phase, achieving directional self-healing of the cracks and overcoming the defect of premature depletion of the surface self-healing phase in the homogeneous doping scheme.

[0076] Example 2 Example 2 of this application provides a method for preparing a ceramic composite material. The process conditions for steps two to four are the same as in Example 1. The main difference from Example 1 is that the molar fraction of Ta in each layer is different (the inner layer is designed with high Ta), and the content of the self-healing phase in the middle layer is adjusted. This example is used to verify the effect of a higher Ta gradient amplitude on the material's resistance to hydrogen reduction and its thermal expansion matching performance.

[0077] The first step is the preparation of the mixed powders for each layer.

[0078] Outer layer mixed powder: based on the outer layer carbide matrix Hf0. 25 Zr0. 20 Ti0. 20 Ta0. 15 Nb0. 20 The proportion of C is as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 3μm are added as a self-healing phase to make the volume fraction of SiC particles in the outer layer 5%. Graphite powder is also added, with the volume fraction of graphite powder in the outer layer mixed powder being 3%.

[0079] Intermediate layer mixed powder: based on intermediate layer carbide matrix Hf0. 25 Zr0. 20 Ti0. 17 Ta0. 22 Nb0. 16The proportions of C are as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 10μm are added as a self-healing phase, so that the volume fraction of SiC particles in the intermediate layer is 18%.

[0080] Inner layer mixed powder: based on inner layer carbide matrix Hf0. 25 Zr0. 20 Ti0. 15 Ta0. 30 Nb0. 10 The proportions of C are as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 20μm are added as a self-healing phase to make the volume fraction of SiC particles in the inner layer 7%. Y2SiO5 powder and SiO2 micro powder are also added. The volume fraction of Y2SiO5 powder in the inner layer mixed powder is 6%, and the volume fraction of SiO2 micro powder in the inner layer mixed powder is 2%.

[0081] In this embodiment, the molar fractions of Ta in the outer, middle, and inner layers are 0.15, 0.22, and 0.30, respectively, satisfying a gradient relationship that increases sequentially from the outer layer to the inner layer. Furthermore, the Ta content in the inner layer is higher than in Example 1, resulting in a larger gradient amplitude. The volume fractions of SiC particles in the outer, middle, and inner layers are 5%, 18%, and 7%, respectively, satisfying a gradient distribution with lower concentrations in the outer layer, higher concentrations in the middle layer, and lower concentrations in the inner layer. The average particle sizes of SiC particles in the outer, middle, and inner layers are 3 μm, 10 μm, and 20 μm, respectively, satisfying a particle size gradient distribution that increases sequentially from the outer layer to the inner layer.

[0082] In this embodiment, the molar fraction of Ta in the inner layer is increased to 0.30, which increases the intrinsic thermal expansion coefficient of the inner layer carbide matrix. However, the Y2Si2O7 phase formed by the in-situ reaction of 6% Y2SiO5 with SiO2 micropowder in the inner layer (with a thermal expansion coefficient of approximately 4.0 × 10⁻⁶) remains relatively stable. -6 K - ¹) and large-particle-size SiC (20 μm, thermal expansion coefficient approximately 4.5 × 10⁻⁶) with a volume fraction of 7%. -6 K - ¹) Its low thermal expansion characteristics effectively offset the thermal expansion increment caused by high Ta. Based on the mixing law of multiphase materials, the overall effective thermal expansion coefficient of the inner layer can still be controlled within 5.5~6.5×10. -6 K - Within the range of ¹, with SiC / SiC substrate (approximately 5.0 × 10⁻⁶). -6 K - ¹) Maintain good thermal expansion matching between them.

[0083] In a reducing atmosphere simulating liquid hydrogen, the high-Ta design of the inner layer further enriches Ta₂O₅ in the oxidation products. Since the hydrogen reduction Gibbs free energy of Ta₂O₅ is more positive than that of HfO₂ and ZrO₂, it exhibits higher thermodynamic stability in a hydrogen-rich atmosphere and is less susceptible to reduction and decomposition by H₂. Therefore, this embodiment forms a more stable anti-hydrogen reduction barrier in the inner layer, exhibiting superior anti-hydrogen reduction performance compared to Embodiment 1. The low-Ta design of the outer layer facilitates the rapid formation of a continuous, dense composite oxide layer dominated by HfO₂ and ZrO₂, ensuring that the high-temperature anti-oxidation protection function of the outer layer remains unaffected. This embodiment is suitable for service scenarios with higher requirements for protection against liquid hydrogen reduction environments.

[0084] Example 3 This application provides a method for preparing a ceramic composite material in Embodiment 3. The main difference from Embodiment 1 is that the self-healing phase particles in the intermediate and inner layers are made of different materials (Si3N4 is used instead of SiC), and the rare earth silicate in the inner layer is different (Lu2SiO5 is used instead of Y2SiO5), in order to verify the influence of different self-healing phase materials and rare earth silicate types on the material properties. The process conditions for steps 2 to 4 are the same as in Embodiment 1.

[0085] The first step is the preparation of the mixed powders for each layer.

[0086] Outer layer mixed powder: based on the outer layer carbide matrix Hf0. 20 Zr0. 20 Ti0. 20 Ta0. 18 Nb0. 22 The proportion of C is as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 3μm are added as a self-healing phase to make the volume fraction of SiC particles in the outer layer 5%. Graphite powder is also added, with the volume fraction of graphite powder in the outer layer mixed powder being 3%.

[0087] Intermediate layer mixed powder: based on intermediate layer carbide matrix Hf0. 20 Zr0. 20 Ti0. 17 Ta0. 22 Nb0. 21 The proportion of C is determined by weighing HfC, ZrC, TiC, TaC and NbC powders, and adding Si3N4 particles with an average particle size of 10μm as a self-healing phase, so that the volume fraction of Si3N4 particles in the intermediate layer is 16%.

[0088] Inner layer mixed powder: based on inner layer carbide matrix Hf0. 20 Zr0. 20 Ti0. 15 Ta0. 28 Nb0.17 The proportions of C are as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 20μm are added as a self-healing phase to make the volume fraction of SiC particles in the inner layer 7%. Lu2SiO5 powder and SiO2 micro powder are also added. The volume fraction of Lu2SiO5 powder in the inner layer mixed powder is 6%, and the volume fraction of SiO2 micro powder in the inner layer mixed powder is 2%.

[0089] In this embodiment, the molar fractions of Ta in the outer, middle, and inner layers are 0.18, 0.22, and 0.28, respectively, satisfying a gradient relationship that increases sequentially from the outer to the inner layer. The volume fraction of SiC in the outer layer is 5%, that of Si3N4 in the middle layer is 16%, and that of SiC in the inner layer is 7%. The average particle size of SiC in the outer layer is 3 μm, that of Si3N4 in the middle layer is 10 μm, and that of SiC in the inner layer is 20 μm.

[0090] In this embodiment, the intermediate layer uses Si3N4 particles with a faster oxidation rate as the self-healing phase. The SiO2 glass phase generated by the oxidation of Si3N4 has lower viscosity and better fluidity, and the N2 gas released during the oxidation process helps the glass phase penetrate and spread in the crack, enabling instantaneous and efficient crack sealing. The inner layer uses Lu2SiO5 with a lower coefficient of thermal expansion, further reducing the overall coefficient of thermal expansion of the inner layer and optimizing the thermal expansion matching with the SiC / SiC substrate. The resulting ceramic composite material has complete gradient characteristics in each layer and good interlayer bonding, making it suitable for service scenarios with higher requirements for the self-healing response speed of the intermediate layer and the thermal expansion matching accuracy of the inner layer.

[0091] Example 4 Example 4 of this application provides a method for preparing a ceramic composite material, which differs from Example 1 in that the type of rare earth silicate in the inner layer is different (Lu2SiO5 is used instead of Y2SiO5) to verify the influence of different rare earth silicate types on the thermal expansion matching performance of the inner layer.

[0092] In this embodiment, Lu2SiO5 is used as the rare earth silicate in the inner layer. During sintering, Lu2SiO5 reacts in situ with SiO2 micropowder to form the Lu2Si2O7 phase. The coefficient of thermal expansion of Lu2Si2O7 is lower than that of Y2Si2O7, which has a stronger offsetting effect on the increase in the coefficient of thermal expansion caused by the high Ta content in the inner layer. This makes the overall coefficient of thermal expansion of the inner layer more compatible with the SiC / SiC substrate, further reducing the interfacial thermal stress between the coating and the substrate and suppressing interfacial debonding and cracking under thermal cycling.

[0093] Example 5 In this embodiment, a multi-channel powder feeding plasma spraying system is used to prepare a gradient coating on the surface of SiC / SiC ceramic matrix composite material.

[0094] First, a SiC transition layer with a thickness of approximately 100 μm was prepared on the surface of a tubular SiC / SiC ceramic matrix composite sample by chemical vapor infiltration.

[0095] Then, three mixed powders were prepared according to the ratio of outer layer, intermediate layer, and inner layer in Example 2, and loaded into three powder feeders. During spraying, the powder feeding rate of the three powder feeders was controlled by a program to sequentially spray the powder onto the SiC transition layer surface: first, the inner layer powder was sprayed to form an inner layer bonded to the substrate; then, the powder feeding rate of the inner layer powder was gradually reduced while the powder feeding rate of the intermediate layer powder was increased to form the intermediate layer; finally, the outer layer powder was gradually introduced to form the outer layer. By controlling the continuous change of the powder feeding rate, a gradient coating with the outer layer, intermediate layer, and inner layer arranged sequentially was constructed in situ along the coating thickness direction (0.5 mm to 2.0 mm), with the outer layer facing the hot side and the inner layer facing the substrate side.

[0096] In this embodiment, the coating has the same three-layer gradient functional partitions as the cast block. The outer layer can rapidly generate a dense composite oxide layer in a high-temperature oxidizing gas flow. The middle layer serves as the core functional layer for crack arrest, and the inner layer can resist the erosion of the liquid hydrogen reducing atmosphere using a Ta2O5-rich oxide layer. The SiC transition layer between the coating and the SiC / SiC substrate, together with the inner rare-earth silicate reaction layer, forms a gradient thermal expansion transition zone, effectively alleviating interfacial thermal stress and suppressing interfacial debonding and cracking during thermal cycling.

[0097] Comparative Example 1 This comparative example provides a single-component HfC-SiC homogeneous composite material.

[0098] First, HfC powder and SiC particles are uniformly mixed according to traditional methods, wherein the volume fraction of SiC particles is 15% and the average particle size is 10μm, without adopting a gradient structure design.

[0099] Then, the mixed powder was loaded into a graphite mold and densified using the same spark plasma sintering process as in Example 1: the sintering temperature was 2000℃, the sintering pressure was 50MPa, the holding time was 30 minutes, and the vacuum degree was 10. -3 Pa, with a heating rate of 100℃ / min, yielded a uniform composite material.

[0100] In this Comparative Example 1, the surface SiC is largely consumed by oxidation during early thermal cycling, and the crack cannot be effectively healed when it propagates inward. The single HfC oxidation product is only HfO2, which is easily reduced by hydrogen in a liquid hydrogen reducing atmosphere, leading to oxide scale damage. It does not contain rare earth silicates and has a compositional gradient transition, resulting in poor thermal expansion matching with the SiC / SiC substrate. Interfacial thermal stress easily leads to debonding, and the overall protective performance is far lower than that of Example 1.

[0101] Comparative Example 2 This comparative example provides a high-entropy carbide-SiC homogeneous composite material with no gradient structure.

[0102] First, according to the equimolar ratio Hf0. 20 Zr0. 20 Ti0. 20 Ta0. 20 Nb0. 20 The proportion of C is as follows: HfC, ZrC, TiC, TaC and NbC powders are weighed out, and SiC particles with an average particle size of 10μm are added as a self-healing phase to make the total volume fraction of SiC particles 15%. They are uniformly mixed without using a gradient structure design.

[0103] Then, the mixed powder was loaded into a graphite mold and densified using the same spark plasma sintering process as in Example 1: the sintering temperature was 2000℃, the sintering pressure was 50MPa, the holding time was 30 minutes, and the vacuum degree was 10. -3 Pa, with a heating rate of 100℃ / min, yielded a uniform composite material.

[0104] In Comparative Example 2, the uniform distribution of the self-healing phase leads to the early consumption of surface SiC during thermal cycling, preventing effective healing as cracks propagate inward. The homogenized Ta content prevents the rapid formation of a dense oxide layer dominated by HfO2 and ZrO2 on the outer layer, and the inner layer cannot accumulate sufficient Ta2O5 to resist liquid hydrogen reduction erosion. The absence of rare-earth silicates and the lack of a compositional gradient result in poor thermal expansion matching with the SiC / SiC substrate, making interfacial thermal stress prone to debonding. Therefore, the overall protective performance is far lower than that of Example 1.

[0105] Comparative Example 3 This comparative example provides a gradient structure composite material that does not contain rare earth silicates.

[0106] Following the gradient structure design of Example 1, outer layer mixed powder, middle layer mixed powder, and inner layer mixed powder were prepared respectively, but Y2SiO5 powder and SiO2 micro powder were not added to the inner layer mixed powder, while the other proportions were the same as in Example 1. The ceramic composite material was obtained using the same process as in Example 1.

[0107] Compared to Example 1, the inner layer of Comparative Example 3 lacks low thermal expansion rare earth silicates, resulting in a slightly higher overall coefficient of thermal expansion and increased interfacial thermal stress between the inner layer and the SiC / SiC substrate due to the difference in thermal expansion coefficients. Simultaneously, the inner layer lacks the dense glassy phase formed by the reaction of rare earth silicates and SiO2, leading to a reduced resistance to hydrogen permeation. Compared to Example 1, this comparative example shows shortcomings in both interfacial thermal stress mitigation and long-term structural stability.

[0108] Comparative Example 4 This comparative example provides a homogeneous SiC composite material with equimolar ratio of pentagonal high-entropy carbides.

[0109] According to the equimolar ratio (Hf0). 20 Zr0. 20 Ta0. 20 Nb0. 20 Ti0. 20 HfC, ZrC, TiC, TaC, and NbC powders were weighed out according to the following proportions. SiC particles with an average particle size of 10 μm were added as a self-healing phase, making the total volume fraction of SiC particles 15%. The mixture was homogeneous without a gradient structure design. The mixed powder was then cold isostatically pressed and sintered in a vacuum sintering furnace at 2100℃ for 120 minutes to obtain a homogeneous composite material.

[0110] Compared to Example 1, Comparative Example 4 did not employ a self-healing phase gradient design, resulting in faster consumption of the surface self-healing phase and reduced healing efficiency during deep crack propagation. Furthermore, it did not employ a Ta element gradient design, limiting the synergistic compatibility between the outer layer's antioxidant properties and the inner layer's reducing properties. Additionally, it lacks rare earth silicates, leading to slightly weaker thermal expansion compatibility with the SiC / SiC substrate, and its overall performance is inferior to Example 1.

[0111] The above description is merely a specific embodiment of this application. Obviously, various modifications and combinations can be made without departing from the spirit and scope of this application. Accordingly, this specification and accompanying drawings are merely exemplary illustrations of this application as defined by the appended claims, and are considered to cover any and all modifications, variations, combinations, or equivalents within the scope of this application. Clearly, those skilled in the art can make various alterations and modifications to this application without departing from the spirit and scope of this application. Thus, if these modifications and modifications of this application fall within the scope of the claims of this application and their equivalents, the intent of this application includes these modifications and modifications. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the protection scope of this application. Therefore, the protection scope of this application should be determined by the protection scope of the stated claims.

Claims

1. A ceramic composite material, characterized in that, The ceramic composite material has an outer layer, a middle layer and an inner layer along the thickness direction. The outer layer, the middle layer and the inner layer all include a carbide matrix and self-healing phase particles dispersed in the carbide matrix. The carbide matrix includes HfC, ZrC, TiC, TaC and NbC. The volume fraction of self-healing phase particles in the outer layer is 3% to 8%, the volume fraction of self-healing phase particles in the middle layer is 12% to 20%, and the volume fraction of self-healing phase particles in the inner layer is 5% to 10%. The mole fraction of Ta in the outer layer is less than that in the middle layer, and the mole fraction of Ta in the middle layer is less than that in the inner layer.

2. The ceramic composite material according to claim 1, characterized in that, The outer layer has a Ta mole fraction of 0.15 to 0.20, the middle layer has a Ta mole fraction of 0.20 to 0.25, and the inner layer has a Ta mole fraction of 0.25 to 0.

35.

3. The ceramic composite material according to claim 1, characterized in that, The average particle size of the self-healing phase particles in the inner layer is greater than that in the middle layer, and the average particle size of the self-healing phase particles in the middle layer is greater than that in the outer layer.

4. The ceramic composite material according to claim 3, characterized in that, The average particle size of the self-healing phase particles in the outer layer is 1 μm to 5 μm, the average particle size of the self-healing phase particles in the middle layer is 5 μm to 15 μm, and the average particle size of the self-healing phase particles in the inner layer is 15 μm to 30 μm.

5. The ceramic composite material according to claim 1, characterized in that, The inner layer also contains rare earth silicates, wherein the volume fraction of the rare earth silicates in the inner layer is 3% to 8%; The outer layer also has a channel structure, which is a continuous interconnected microchannel.

6. The ceramic composite material according to claim 1, characterized in that, The outer layer has a thickness of 0.5mm to 2.0mm, the middle layer has a thickness of 1.0mm to 5.0mm, and the inner layer has a thickness of 0.1mm to 0.5mm.

7. The ceramic composite material according to any one of claims 1 to 6, characterized in that, The self-healing phase particles are selected from SiC particles and / or Si3N4 particles.

8. A method for preparing a ceramic composite material according to any one of claims 1 to 7, characterized in that, include: Outer layer premix, middle layer premix and inner layer premix were prepared using carbide matrix and self-healing phase particles, respectively. The inner layer premix, the middle layer premix, and the outer layer premix are sequentially stacked and dried to obtain a gradient green body; The gradient green body is subjected to debinding and sintering to obtain a ceramic composite material.

9. The method for preparing the ceramic composite material according to claim 8, characterized in that, The preparation of outer layer premix, middle layer premix, and inner layer premix using a carbide matrix and self-healing phase particles includes: Outer layer mixed powder, middle layer mixed powder and inner layer mixed powder were prepared by using carbide matrix and self-healing phase particles respectively; The outer layer mixed powder, the middle layer mixed powder, and the inner layer mixed powder are ball-milled and mixed to obtain an outer layer slurry, a middle layer slurry, and an inner layer slurry. The outer layer slurry, the middle layer slurry, and the inner layer slurry are dried and sieved respectively to obtain the outer layer premix, the middle layer premix, and the inner layer premix.

10. The method for preparing the ceramic composite material according to claim 8 or 9, characterized in that, The process of debinding and sintering the gradient green body to obtain a ceramic composite material includes: In a vacuum or inert atmosphere, the gradient green body is subjected to a debinding treatment at 600℃~800℃ to obtain a debinded green body; wherein the debinding treatment time is 1 hour~3 hours. The debinding green body is sintered at a temperature of 1800℃~2200℃ and a pressure of 30MPa~100MPa using spark plasma sintering technology, and held at that temperature for 10 minutes~60 minutes to obtain a ceramic composite material.